Transforming Hate into Compassion as an Islamic Nonviolent Thought of Bediüzzaman Said Nursi - Ziaulhaq, Mochamad; Sen, Hasbi (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2021)
The study of hatred that emerges as human nature can provide an analytical picture of how hatred arises, develops, and turns into humanitarian incidents. With an in-depth, systematic, and genealogical study, it can come up with a panacea for this hatred. The elixir can turn hatred into compassion, violence into nonviolence, and find creative ways to turn conflict into peace; thus, creating a new, better reality. This qualitative research uses a literature study from Risale-i Nur by Bediüzzaman Said Nursi (1877-1960). In this study, Nursi's religious and psychological explanations are compared with religious theories and studies of peace and conflict that are already popular in the Western world. The data in Risale-i Nur were analysed using the Mimesis theoretical framework of the philosophical approach. With this analysis there is the prefiguration stage (Mimesis I) about the background of Said Nursi's life, the configuration stage (Mimesis II) about the story of Said Nursi's traumatic experience, and the transfiguration stage about the emergence of the capacity to handle conflict independently with others using nonviolent ideas creatively, thus creating a new reality (Mimesis III). This new reality is